2011
DOI: 10.5530/pj.2011.26.12
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacognostic and Phytochemical Evaluation of Citrus aurantifolia (Christm) Swingle PEEL

Abstract: It is an evergreen, spiny shrub or small tree 5 to 6 m in height. The plant has single or multiple stems and irregular branches covered with smoothish brown to gray bark. The twigs are quadrangular (when young), green, and bare sharp axillary spines 3 to 17 mm long. The leaves are yellow-green to dark green, with 5-to 28-mm winged petioles and elliptic to oval leathery 4-to 13-cm long blades with edges that have minute rounded teeth. The crushed foliage has a strong,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 1 publication
0
22
0
4
Order By: Relevance
“…The fluorescence analysis is helpful in the characterization of crude drugs 10 and further reveals the presence of active agents in the leaf and stem by their various colour reactions to different chemicals and colour change under the UV at 254 and 366 nm. Though the information, studies on the biological and chemical activities of T. africanum is very scanty, the result in this study will further help in identifying the purity, correct identification of the crude drug, the standardisation and control of T. africanum (Tables 2 and 3).…”
Section: Resultsmentioning
confidence: 99%
“…The fluorescence analysis is helpful in the characterization of crude drugs 10 and further reveals the presence of active agents in the leaf and stem by their various colour reactions to different chemicals and colour change under the UV at 254 and 366 nm. Though the information, studies on the biological and chemical activities of T. africanum is very scanty, the result in this study will further help in identifying the purity, correct identification of the crude drug, the standardisation and control of T. africanum (Tables 2 and 3).…”
Section: Resultsmentioning
confidence: 99%
“…Biji berbentuk bulat telur, pipih, putih, putih kehijauan (Syamsulhidayat dan Hutapea, 1991). Secara taksonomi, tanaman jeruk nipis (Citrus aurantifolia) termasuk dalam famili Rutaceae (Apraj et al, 2011). (Ferguson, 1990;Nwachukwu et al, 2007 (Aibinu, 2007;Khare, 2007…”
Section: Pendahuluanunclassified
“…A similar study targeting red chillies as the recipient plants conducted by Sahoo et al [15] using leaf extract of Citrus reticulata found germination inhibition of the recipient plants up to 55%. Previously, phytochemical screening against the leaves extract of C. reticulata has been done and resulted several secondary metabolites allegedly allelopathic such as flavonoids, tannins, steroids, and phenolic compound [16]. Aqueous extract of kaccholam rhizome, as indicated by Narasinga Rao and Kaladhar [14] in fact contains some of the compounds including tannins and phenols.…”
Section: Concentration Of Extractmentioning
confidence: 99%